Predictors of failure to reach target sample size in surgical randomized trials. Issue 2 (3rd December 2021) - Chadow, David; Robinson, N Bryce; Cancelli, Gianmarco; Soletti, Giovanni; Audisio, Katia; Rahouma, Mohamed; Perezgrovas, Roberto; Gaudino, Mario
Abstract : It is estimated that 25–30 per cent of RCTs fail to reach their target sample size. Multicentre design, publication year, and commercial sponsor were inversely associated with failure to reach the target sample size. A substantial proportion of surgical trials fail reach target sample size, but the trend is showing improvement.